MODEL HUBUNGAN ASPEK PSIKOSOSIAL DAN AKTIFITAS FISIK DENGAN STATUS GIZI LANSIA - Rusilanti Rusilanti; Clara Meliyanti Kusharto (Food and Nutrition Society of Indonesia, 2006)
The aims of this research was to analyze the correlation of psychosocial and physical aspect with nutritional status of the elderly reside in community dwelling. The site of study was purposively selected at three “kelurahan” : Budi agung, Baranangsiang, and Situ Gede in Bogor City. A total of 100 elderly (age range 60 – 85 years; mean 68.4 year) were actively participated. A Structural Equation Modelling (SEM) Lisrel program was used to analyse the data. The study showed positive correlation of psychosocial (r=0.07) and physical aspect (r=0.04) with nutritional status of the elderly in community.